Method for simulating preparation of industrial iron pollution catalytic cracking catalyst
Through the two-cycle aging metal loading method and a small number of multiple cycle loading mode, organometallic iron is deposited on the catalyst surface to generate iron tumors similar to industrial balancers, solving the problem of difficult to simulate iron pollution in industrial catalysts in the existing technology, and real simulation of iron distribution and valence state in the catalyst is achieved.
Patent Information
- Application Number
- CN202311113729.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The prior art is difficult to accurately simulate the iron contamination state of industrial catalytic cracking catalysts in the laboratory, including the distribution location of heavy metal iron, valence distribution and iron tumor formation on the surface of the catalyst.
The two-cycle aging metal loading method is used, firstly the alkali metal, alkaline earth metal or transition metal is loaded, and then the iron metal is loaded, and the organic metal is deposited on the catalyst surface through a small number of multiple cycles, forming an iron tumor similar to the industrial balancer.
The distribution position and valence distribution of iron in the catalyst are achieved in a state similar to that of industrial iron pollution balancers, which can truly simulate the iron pollution situation of industrial catalysts and provide more accurate performance evaluation.
Smart Images

Figure CN119524865A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a laboratory aging pretreatment method for fresh catalysts in the field of catalytic cracking, and more specifically to a method for simulating the preparation of industrial iron-contaminated catalytic cracking catalysts. Background Art
[0002] In recent years, as the world's crude oil has become heavier and inferior, most refineries have begun to develop catalytic cracking technology (FCC) for blending or refining heavy oil and residual oil. The content of harmful metals in heavy oil or residual oil is much higher than that in distillate oil. Harmful metals such as iron, sodium, calcium, nickel and vanadium, which exist in the form of porphyrin compounds, cyclohexane salts, inorganic salts, etc. in the raw oil, are continuously deposited on the surface of the catalyst through the long-term re-reaction process in industrial equipment. The catalyst is poisoned by destroying the crystal structure, blocking the pores, covering the active sites, etc.
[0003] Heavy metal nickel and vanadium pollution has become a long-term concern. Iron poisoning of catalytic cracking catalysts has also begun to attract people's attention. Some refineries have already experienced iron poisoning in actual production. As the catalytic cracking unit is gradually becoming more and more polluted by iron, the industrial unit mainly exhibits the following symptoms: increased slurry yield, decreased conversion rate, increased dry gas and hydrogen yields, decreased gasoline and diesel yields, etc. On the other hand, as the iron contamination on the catalyst increases, a large number of tumor-like protrusions will form on the surface of the catalyst, covering the pores of the catalyst, causing the equilibrium catalyst fluidization properties to deteriorate and the apparent bulk density to decrease.
[0004] Therefore, it is necessary to prepare catalytic cracking catalysts with resistance to heavy metal iron pollution through laboratory research to cope with the increasing trend of heavy metal iron pollution. The design of catalysts with resistance to heavy metal iron pollution can be completed in the laboratory, but how to achieve comprehensive simulation from fresh agents to industrial device iron pollution balance agents through effective simulation means in the laboratory has become an urgent issue of concern. The simulation of iron pollution balance agents not only includes the simulation of the iron loading on the catalyst and the valence state of iron, but more importantly, it can achieve the simulation of the formation of iron nodules on the catalyst surface.
[0005] The Mitchell equal volume impregnation method is a simple simulation method for catalytic cracking catalysts to resist heavy metal pollution. The specific method is to use an equal volume of heavy metal compound solution to impregnate the fresh catalyst in the laboratory, then calcine at low temperature to make the catalyst evenly dried, and then use high temperature calcination to remove the dissolved heavy metals and heavy metal element complexes, and finally only deposit the heavy metals on the catalyst, and finally obtain the final aged catalyst after hydrothermal aging. This method is simple to operate, but it also has the following shortcomings: (1) The heavy metal deposition achieved by the impregnation method runs through the inside and outside of the catalyst and is uniformly distributed throughout the catalyst particles, rather than the heavy metal elements on the industrial balance agent being distributed in different positions from the outside to the inside due to gradual deposition; (2) Since the impregnation method deposits heavy metal elements on the catalyst through high-temperature roasting in air, heavy metals such as nickel, vanadium, and iron are all in the highest valence state, and it is impossible to simulate the valence state distribution of heavy metals on the balance agent; (3) Since the impregnation method loads all metals on the catalyst surface at once, it does not simulate the multiple cycle reactions of industrial equipment. On the other hand, there is no environment on the catalyst that is conducive to the deposition of heavy metal iron, and it is difficult to simulate iron nodules on the catalyst surface by the impregnation method.
[0006] Albemarle has designed a CD cycle deactivation device to simulate the effect of heavy metal pollution on catalyst activity. It consists of a fixed bed reactor, which is loaded with 100g to 200g of catalyst at a time. It is deactivated through repeated cracking, stripping and regeneration cycles. VGO / VR raw materials mixed with organic heavy metals are used in the cracking stage. After the reaction is completed, nitrogen or water vapor is used for stripping, and finally water vapor / N2 / O2 and other (such as SO x ) gas mixture was regenerated at 788℃ for 30min. The balance agent was simulated by multiple cycles. This method can achieve the position distribution of heavy metal iron on the catalyst, but it cannot achieve the valence distribution of heavy metal iron element in industrial catalysts. On the other hand, it is difficult to induce iron nodules on the catalyst surface.
[0007] Du Quansheng et al. (Petroleum Refining and Chemical Engineering, 2007.2) conducted SEM and EDS analysis on iron-contaminated balance agents collected from industrial devices and iron-contaminated catalysts prepared in the laboratory, and found that there were significant differences in the distribution of iron produced by different iron sources on the catalyst. Among them, the iron-contaminated catalyst prepared in the laboratory used ferric chloride and ferric cyclopentaneate as iron sources, and was prepared by impregnation method and circulation pollution method respectively. The article used a high-resolution scanning electron microscope to observe the iron-contaminated catalyst collected from the industrial device, and found obvious iron nodules on its surface. However, the formation of iron nodules was not observed on the artificial iron-contaminated catalyst in the laboratory. It was only through EDS energy spectrum analysis that it was found that when ferric cyclopentaneate was deposited on the catalyst by cyclic loading, it was mainly present in the outer layer of the catalyst particles.
[0008] Liu Qianqian et al. (Petroleum Refining and Chemical Engineering, 2018.5) used the cyclic pollution function of the ACE-D100 device to contaminate the metal onto the catalyst in 6 batches. After repeated reaction-stripping-regeneration to achieve the target average metal pollution, the catalyst was taken out and subjected to a certain number of cycles of redox cycle hydrothermal post-treatment to finally obtain a laboratory aging agent. The problem with this method is that the aging process of the catalyst in the industrial device is divided into two separate stages, that is, first the heavy metal loading is achieved through multiple reaction and regeneration cycles, and then the hydrothermal aging post-treatment is completed. The disadvantage of this method is that it does not simulate the continuous heavy metal pollution and hydrothermal aging process on the industrial device. Metal loading and hydrothermal aging are carried out separately, and the device cannot be operated continuously, resulting in a longer catalyst treatment cycle. In addition, the treatment temperature of the catalyst for redox cycle is 780°C, and the atmosphere changes in one redox cycle are as follows: 10 minutes of nitrogen stripping, 10 minutes of oxidizing gas treatment, 10 minutes of nitrogen stripping, and 10 minutes of reducing gas treatment, and water vapor with a volume fraction of 60% is present in all four steps; finally, a laboratory aging agent is prepared. This method is the same as the CPS aging method developed by Grace Davison. The disadvantage is that although the redox cycle treatment is carried out, the first step of each cycle is oxidation, so that the heavy metals on the catalyst are hydrothermally aged in a high valence state, which aggravates the destructive effect of the same amount of heavy metals nickel and vanadium on the catalyst, reduces the thermal stability of the catalyst, and easily leads to sintering of catalyst particles.
[0009] In summary, although the prior art uses various methods to conduct laboratory simulation studies on iron contamination of fresh catalysts, the catalysts obtained by these methods do not have the characteristics of the distribution position of heavy metal iron on the industrial iron pollution balance agent, the valence distribution of iron, and the formation of iron nodules on the catalyst surface. Therefore, it is difficult to accurately evaluate the performance of the prepared metal-resistant catalytic cracking catalyst. Summary of the invention
[0010] The main purpose of the present invention is to provide a method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst. In the catalyst obtained by the method of the present invention, the distribution position of iron and the distribution of the valence state of iron are similar to those of an industrial iron-contaminated balance agent, which can provide strong support for practical industrial applications.
[0011] In order to achieve the above object, the present invention provides a method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst, comprising the following steps:
[0012] Step 1, reacting the first feedstock oil with a fresh catalytic cracking catalyst, then stripping to remove hydrocarbon oil gas, then performing charring regeneration, then stripping to cool, and then allowing the treated catalytic cracking catalyst to cycle with the first feedstock oil to perform a reaction, stripping, regeneration, and stripping process, the number of cycles being at least one;
[0013] Step 2, reacting the second raw oil with the catalytic cracking catalyst obtained in step 1, then stripping to remove hydrocarbon oil gas, then performing charring regeneration, then stripping to cool, and then allowing the treated catalytic cracking catalyst to cycle with the second raw oil to perform reaction, stripping, regeneration, and stripping, the number of cycles being at least one;
[0014] Step 3, subjecting the catalytic cracking catalyst obtained in step 2 to a hydrothermal aging treatment to obtain an industrial iron-contaminated catalytic cracking catalyst;
[0015] Wherein, alkali metal compounds, alkaline earth metal compounds and / or transition metal compounds other than iron are added to the first feedstock oil, and iron-containing compounds are added to the second feedstock oil.
[0016] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst described in the present invention comprises: the alkali metal compound is a sodium-containing organic compound, the alkaline earth metal compound is a calcium-containing organic compound, the transition metal compound other than iron is at least one of a nickel-containing organic compound, a vanadium-containing organic compound, and a copper-containing organic compound; and the iron-containing compound is an iron-containing organic compound.
[0017] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst described in the present invention comprises the following steps: the alkali metal compound is sodium isooctanoate and / or sodium cyclopentaneate, the alkaline earth metal compound is calcium stearate, the transition metal compound other than iron is nickel cyclopentaneate, vanadium cyclopentaneate or copper cyclopentaneate; and the iron-containing compound is at least one of iron cyclopentaneate, iron stearate and ferrocene.
[0018] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst of the present invention comprises the following steps: the metal concentration in the first feedstock oil is 100 μg / g to 2000 μg / g in terms of metal; and the metal concentration in the second feedstock oil is 100 μg / g to 2000 μg / g in terms of metal.
[0019] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst of the present invention comprises the following steps: the first raw oil reacts with a fresh catalytic cracking catalyst after preheating, the preheating temperature is 60°C to 90°C, the reaction temperature is 490°C to 530°C, the catalyst-to-oil ratio is 5 to 30, the single cycle oil feeding time is 1 min to 5 min, and the mass flow rate of the first raw oil is 5 g / min to 15 g / min; the second raw oil reacts with the catalytic cracking catalyst obtained in step 1 after preheating, the preheating temperature is 60°C to 90°C, the reaction temperature is 490°C to 530°C, the catalyst-to-oil ratio is 5 to 30, the single cycle oil feeding time is 1 min to 5 min, and the mass flow rate of the first raw oil is 5 g / min to 15 g / min.
[0020] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst of the present invention, wherein, in step 1, the stripping to remove hydrocarbon oil and gas and the stripping cooling are both carried out under the action of nitrogen, the nitrogen flow rate is 500ml / min~1500ml / min, and the nitrogen stripping time is 1min~10min; the temperature of the char regeneration is 680℃~740℃, and the char regeneration time is 20min~40min.
[0021] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst of the present invention, wherein, in step 2, the stripping to remove hydrocarbon oil and gas and the stripping cooling are both carried out under the action of nitrogen, the nitrogen flow rate is 500ml / min~1500ml / min, and the nitrogen stripping time is 1min~10min; the temperature of the char regeneration is 680℃~740℃, and the char regeneration time is 20min~40min.
[0022] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to the present invention, wherein the hydrothermal aging treatment process in step 3 comprises:
[0023] The catalytic cracking catalyst obtained in step 2 is treated with a reducing gas, then treated with nitrogen, then treated with an oxidizing gas, and then treated with nitrogen. The process of treating with a reducing gas, treating with nitrogen, treating with an oxidizing gas, and treating with nitrogen is then repeated at least once to obtain an industrial iron-contaminated catalytic cracking catalyst.
[0024] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst of the present invention, wherein a certain amount of water vapor is introduced into the catalytic cracking catalyst obtained in step 2 during the process of being treated with a reducing gas, a nitrogen gas, and an oxidizing gas, and the mass ratio of water vapor to reducing gas, water vapor to nitrogen, and water vapor to oxidizing gas is 30:70-55:45; the oxidizing gas includes one or more of high-purity air, oxygen in nitrogen, and sulfur dioxide in nitrogen; the selected reducing gas includes one or more of hydrogen in nitrogen, propylene in nitrogen, and carbon monoxide in nitrogen; the The temperature of the reducing gas treatment is 700°C to 770°C, the time is 2min to 7min, and the flow rate of the reducing gas is 500ml / min to 1500ml / min; the temperature of the nitrogen treatment is 700°C to 770°C, the time is 1min to 10min, and the flow rate of the nitrogen is 500ml / min to 1500ml / min; the temperature of the oxidizing gas treatment is 700°C to 770°C, the time is 2min to 7min, and the flow rate of the oxidizing gas is 500ml / min to 1500ml / min.
[0025] The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst of the present invention comprises the following steps: step 1 is repeated 10 to 40 times, step 2 is repeated 100 to 300 times, and step 3 is repeated 75 to 120 times.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention uses a two-cycle aging metal loading method. The first step is to load alkali metals, alkaline earth metals or transition metals other than iron, and the second step is to load iron metal. The loading of the metal in the first step can create a favorable environment for the loading of heavy metal iron on the catalyst surface.
[0028] (2) Furthermore, the present invention uses a small amount of multiple cyclic loading mode when carrying out the second step of heavy metal iron cyclic loading. A relatively low amount of organic metal iron is loaded in a single cycle. Through multiple cycles, the organic metal iron can be gradually deposited on the catalyst surface to generate iron nodules similar to those unique to industrial balance agents, thereby simulating the distribution state of organic metal iron on industrial balance agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an electron microscope picture of the LDR-600SR industrial balance agent of Comparative Example 1 of the present invention;
[0030] Figure 2 This is an electron microscope picture of the aging simulator of Example 1 of the present invention;
[0031] Figure 3 This is an electron microscope picture of the aging simulator of Comparative Example 2 of the present invention;
[0032] Figure 4 This is an electron microscope picture of the aging simulator of Comparative Example 3 of the present invention;
[0033] Figure 5 This is an electron microscope picture of the aging simulator of Comparative Example 4 of the present invention;
[0034] Figure 6 This is an electron microscope picture of the aging simulator of Comparative Example 5 of the present invention;
[0035] Figure 7 This is an electron microscope picture of the aging simulator of Comparative Example 6 of the present invention;
[0036] Figure 8 This is an electron microscope picture of the aging simulator of comparative example 7 of the present invention. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention is described in detail below. The following implementation modes are implemented on the premise of the technical scheme of the present invention, and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following implementation modes. The structures or experimental methods of specific conditions are not specified in the following implementation modes, and generally conventional conditions are followed.
[0038] The present invention provides a method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst, comprising the following steps:
[0039] Step 1, reacting the first feedstock oil with a fresh catalytic cracking catalyst, then stripping to remove hydrocarbon oil gas, then performing charring regeneration, then stripping to cool, and then allowing the treated catalytic cracking catalyst to cycle with the first feedstock oil to perform a reaction, stripping, regeneration, and stripping process, the number of cycles being at least one;
[0040] Step 2, reacting the second raw oil with the catalytic cracking catalyst obtained in step 1, then stripping to remove hydrocarbon oil gas, then performing charring regeneration, then stripping to cool, and then allowing the treated catalytic cracking catalyst to cycle with the second raw oil to perform reaction, stripping, regeneration, and stripping, the number of cycles being at least one;
[0041] Step 3, subjecting the catalytic cracking catalyst obtained in step 2 to a hydrothermal aging treatment to obtain an industrial iron-contaminated catalytic cracking catalyst;
[0042] Wherein, alkali metal compounds, alkaline earth metal compounds and / or transition metal compounds other than iron are added to the first feedstock oil, and iron-containing compounds are added to the second feedstock oil.
[0043] The present invention uses a two-cycle aging metal loading method, wherein the first step is to load alkali metals, alkaline earth metals or transition metals other than iron, and the second step is to load iron metal. The loading of the metal in the first step can create a favorable environment for the loading of heavy metal iron on the catalyst surface. The catalytic cracking catalyst obtained by the method of the present invention has similar characteristics to the industrial iron pollution balance catalyst and can be used to replace the process iron pollution balance catalyst for evaluation.
[0044] The present invention has no restrictions on the type of catalytic cracking catalyst to be treated. Any commonly used catalytic cracking catalyst can be used. For example, the zeolite molecular sieve is selected from one or more of REY, REX, REHY, USY, REUSY, HZSM-5, REZSM-5, REHZSM-5, and β zeolite molecular sieves, and the binder is selected from one or more of silica-alumina gel, silica sol, aluminum sol, silica-alumina sol, boehmite, and pseudo-boehmite. The clay material is selected from one or more of kaolin, halloysite, montmorillonite, diatomaceous earth, saponite, rectorite, sepiolite, attapulgite, hydrotalcite, and bentonite. The catalytic cracking catalyst made from the above raw materials can be treated by the method provided by the present invention, and the treated catalyst can be a single catalyst or a mixture of two or more catalysts.
[0045] In the present invention, alkali metal compounds, alkaline earth metal compounds and / or transition metal compounds other than iron are added to the first stock oil. The first stock oil can be one or more of the commonly used catalytic cracking stock oils. For example, straight-run diesel, catalytic diesel, hydrogenated diesel, vacuum gas oil, atmospheric residue, coker gas oil, deasphalted oil, etc., preferably straight-run diesel, hydrogenated diesel or a mixture thereof.
[0046] In one embodiment, the alkali metal compound is a sodium-containing organic compound, more specifically, an oil-soluble sodium-containing organic compound, such as sodium isooctanoate and / or sodium cyclopentaneate; the alkaline earth metal compound is a calcium-containing organic compound, more specifically, an oil-soluble calcium-containing organic compound, such as calcium stearate; the transition metal compound other than iron is at least one of a nickel-containing organic compound, a vanadium-containing organic compound, and a copper-containing organic compound, more specifically, at least one of an oil-soluble nickel-containing organic compound, a vanadium-containing organic compound, and a copper-containing organic compound, such as nickel cyclopentaneate, vanadium cyclopentaneate, or copper cyclopentaneate.
[0047] The amount of alkali metal compound, alkaline earth metal compound and / or transition metal compound other than iron added to the first feedstock oil is calculated based on the amount of fresh catalytic cracking catalyst, the metal amount of the target industrial equilibrium catalyst, the single cycle oil feeding time, the oil feeding flow rate and the total number of cycles. In one embodiment, the metal concentration in the first feedstock oil of the present invention is 100 μg / g to 2000 μg / g, preferably 300 μg / g to 1200 μg / g.
[0048] The first feedstock oil reacts with the fresh catalytic cracking catalyst after preheating, and the preheating temperature is 60°C to 90°C, preferably 70°C to 80°C. In one embodiment, the first feedstock oil is introduced into the reactor through an oil feed pump under the lifting effect of high-purity nitrogen to react with the fresh catalytic cracking catalyst. The reaction temperature is 490°C to 530°C, preferably 500°C to 515°C, the catalyst-oil ratio is 5 to 30, preferably 10 to 20, the single cycle oil feeding time is 1min to 5min, preferably 1.33min to 1.5min, and the mass flow rate of the first feedstock oil is 5g / min to 15g / min, preferably 6g / min to 7.5g / min.
[0049] After the first feedstock oil reacts with the fresh catalytic cracking catalyst, the hydrocarbon oil gas is stripped. In one embodiment, the stripping gas is nitrogen, the flow rate of nitrogen is 500ml / min to 1500ml / min, preferably 880ml / min to 1020ml / min, and the nitrogen stripping time is 1min to 10min, preferably 2min to 4min. After nitrogen stripping, the temperature is raised to the charring temperature for charring regeneration. In one embodiment, the regeneration is carried out in an oxidizing gas atmosphere, and the oxidizing gas includes, for example, one or more gases of high-purity air, oxygen in nitrogen, sulfur dioxide in nitrogen, and other gases with oxidizing ability. The regeneration temperature is 680℃ to 740℃, preferably 700℃ to 720℃, and the regeneration time is 20min to 40min, preferably 30min to 35min. After regeneration, stripping is performed again to cool down to the reaction temperature. The stripping gas is nitrogen. The flow rate of nitrogen is 500ml / min to 1500ml / min, preferably 880ml / min to 1020ml / min. The nitrogen stripping time is 1min to 10min, preferably 2min to 4min.
[0050] After the stripping and cooling in step 1, a reaction process is completed. The above reaction, stripping, regeneration, and stripping process are repeated at least once. Here, one cycle refers to a reaction, stripping, regeneration, and stripping process. In one embodiment, the number of cycles is 10 to 40 times, preferably 20 to 30 times. After multiple cycles, alkali metals, alkaline earth metals, and other transition metals except iron are loaded on the catalyst surface.
[0051] Step 2 is: reacting the second raw oil with the catalytic cracking catalyst obtained in step 1, then stripping to remove hydrocarbon oil gas, then burning and regenerating, then stripping and cooling to complete a reaction process; then making the fresh catalytic cracking catalyst and the first raw oil cycle to react, strip, regenerate, and strip, the number of cycles is at least one.
[0052] The present invention uses a small amount of multiple cyclic loading mode when carrying out the second step of heavy metal iron cyclic loading, loading a relatively low amount of organic metal iron in a single cycle, and allowing the organic metal iron to gradually deposit on the catalyst surface through multiple cycles to generate iron nodules similar to those unique to industrial balancers, thereby simulating the distribution state of organic metal iron on industrial balancers.
[0053] In the present invention, an iron-containing compound is added to the second stock oil. The second stock oil can be one or more of the commonly used catalytic cracking stock oils. For example, straight-run diesel, catalytic diesel, hydrogenated diesel, vacuum gas oil, atmospheric residue, coker gas oil, deasphalted oil, etc., preferably straight-run diesel, hydrogenated diesel or a mixture thereof. Except for the added metal compound, the second stock oil can be the same as the first stock oil.
[0054] The iron-containing compound is an iron-containing organic compound, more specifically, an oil-soluble iron-containing organic compound, such as at least one of iron cyclopentaneate, iron stearate, and ferrocene.
[0055] The amount of the iron-containing compound added to the second feedstock oil is calculated based on the amount of fresh catalytic cracking catalyst added, the iron content of the target industrial equilibrium catalyst, the single cycle oil feeding time, the oil feeding flow rate, and the total number of cycles. In one embodiment, the iron concentration in the second feedstock oil of the present invention is 100 μg / g to 2000 μg / g, preferably 500 μg / g to 1200 μg / g.
[0056] The second feedstock oil reacts with the catalytic cracking catalyst obtained in step 1 after preheating, and the preheating temperature of the second feedstock oil is 60°C to 90°C, preferably 70°C to 80°C. In one embodiment, the second feedstock oil is introduced into the reactor through an oil feed pump under the lifting effect of high-purity nitrogen to react with the catalytic cracking catalyst obtained in step 1. The catalytic cracking reaction temperature is 490°C to 530°C, preferably 500°C to 515°C; the catalyst-oil ratio is 5 to 30, preferably 10 to 20; the single cycle oil feeding time is 1min to 5min, preferably 1.33min to 1.5min; the mass flow rate of the second feedstock oil is 5g / min to 15g / min, preferably 6g / min to 7.5g / min.
[0057] After the second feedstock oil reacts with the catalytic cracking catalyst obtained in step 1, the hydrocarbon oil gas is stripped. In one embodiment, the stripping gas is nitrogen, the flow rate of nitrogen is 500ml / min to 1500ml / min, preferably 880ml / min to 1020ml / min, and the nitrogen stripping time is 1min to 10min, preferably 2min to 4min. After nitrogen stripping, the temperature is raised to the charring temperature for charring regeneration. In one embodiment, the regeneration is carried out in an oxidizing gas atmosphere, and the oxidizing gas includes, for example, one or more gases of high-purity air, oxygen in nitrogen, sulfur dioxide in nitrogen, and other gases with oxidizing ability. The regeneration temperature is 680℃ to 740℃, preferably 700℃ to 720℃, and the regeneration time is 20min to 40min, preferably 30min to 35min. After regeneration, stripping is performed again to cool down to the reaction temperature. The stripping gas is nitrogen. The flow rate of nitrogen is 500ml / min to 1500ml / min, preferably 880ml / min to 1020ml / min. The nitrogen stripping time is 1min to 10min, preferably 2min to 4min.
[0058] After the stripping and cooling in step 2, a reaction process is completed. The above reaction, stripping, regeneration, and stripping process are cyclically carried out for at least one cycle. Cycling once here means carrying out a reaction, stripping, regeneration, and stripping process. In one embodiment, the number of cycles is 100 to 300 times, preferably 150 to 200 times. After multiple cycles, iron is loaded on the catalyst surface.
[0059] Step 3 is: subjecting the catalytic cracking catalyst obtained in step 2 to hydrothermal aging treatment to obtain an industrial iron-contaminated catalytic cracking catalyst.
[0060] In one embodiment, the hydrothermal aging process of the present invention uses gases with oxidizing and reducing properties, so that the valence states of organic metal iron and other metals on the catalyst are distributed in high and low states rather than a single high-valence state, simulating the valence state distribution characteristics of organic metals on industrial balance agents.
[0061] In another embodiment, in the hydrothermal aging process of the present invention, a reducing gas is first introduced to age the catalyst, then nitrogen is used for stripping for a period of time, and then the catalyst is switched to an oxidizing gas for treatment. The sequence of reduction followed by oxidation can avoid hydrothermal aging of the heavy metals on the catalyst in a high-valence state at the beginning of each cycle, thereby reducing the destructive effects of the same amount of heavy metals nickel and vanadium on the catalyst.
[0062] In one embodiment, the hydrothermal aging treatment process in step 3 includes:
[0063] The catalytic cracking catalyst obtained in step 2 is treated with a reducing gas, then treated with nitrogen, then treated with an oxidizing gas, and then treated with nitrogen. The process of treating with a reducing gas, treating with nitrogen, treating with an oxidizing gas, and treating with nitrogen is then repeated at least once to obtain an industrial iron-contaminated catalytic cracking catalyst.
[0064] In one embodiment, a certain amount of water vapor is introduced into the catalytic cracking catalyst obtained in step 2 during the treatment with reducing gas, nitrogen and oxidizing gas, and the weight ratio of water vapor to reducing gas, water vapor to nitrogen and water vapor to oxidizing gas is 30:70-55:45, preferably 40:60-50:50; the oxidizing gas is a gas with oxidizing ability, for example, one or more of high-purity air, oxygen in nitrogen and sulfur dioxide in nitrogen; the reducing gas is a gas with reducing ability, for example, one or more of hydrogen in nitrogen, propylene in nitrogen and carbon monoxide in nitrogen; the temperature for the treatment with reducing gas is 700° C. to 770° C., and the time is 2 min to 7 min, preferably 3 min to 4 min. 5min, the flow rate of reducing gas is 500ml / min~1500ml / min, preferably 880ml / min~1020ml / min; the temperature of nitrogen treatment is 700℃~770℃, the time is 1min~10min, preferably 2min~4min, the flow rate of nitrogen is 500ml / min~1500ml / min, preferably 880ml / min~1020ml / min; the temperature of oxidizing gas treatment is 700℃~770℃, the time is 2min~7min, preferably 3min~5min, and the flow rate of oxidizing gas is 500ml / min~1500ml / min, preferably 880ml / min~1020ml / min.
[0065] Among them, "oxygen in nitrogen" means oxygen mixed in nitrogen, and other expressions are similar.
[0066] Here, repeating once means performing the process of treating with reducing gas, treating with nitrogen, treating with oxidizing gas, and treating with nitrogen once. In one embodiment, step 3 is repeated 75 to 120 times, preferably 85 to 100 times.
[0067] In one embodiment, the method of the present invention is carried out on a catalytic cracking unit. Any catalytic cracking unit designed based on the fixed fluidized bed principle, such as a fixed fluidized bed evaluation unit partially modified to conduct catalyst circulation pollution, is a suitable test device for the present invention. In another embodiment, the method of the present invention is carried out on an MCD circulation aging device.
[0068] The method provided by the present invention utilizes a circulating aging device. Except for the manual operations of configuring the crude oil and adding and unloading the agent, all other operations are completed automatically and continuously. The operation is simple and can greatly save time and manpower.
[0069] In addition, the iron pollution simulating agent obtained by pre-treating the fresh catalyst using the present invention can simulate the state of the industrial iron pollution balancing agent from multiple angles such as the simulation of iron nodule formation, the distribution position of iron, and the distribution of iron valence. The results obtained by analyzing and evaluating such aging simulating agents are more instructive, indicating the direction for scientific research and providing strong support for practical industrial applications.
[0070] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited thereto. The LDR-600SR fresh catalytic cracking catalyst used in the examples and comparative examples is produced by the catalyst plant of PetroChina Lanzhou Petrochemical Company. The LDR-600SR iron pollution industrial balance agent is provided by Dalian West Pacific Petrochemical Co., Ltd.
[0071] Comparative Example 1
[0072] This comparative example uses the ACE-MODEL C evaluation device to evaluate the product distribution of the LDR-600SR industrial balance agent. Take 9g of the above LDR-600SR industrial balance agent to conduct the ACE evaluation agent-oil ratio experiment. The agent-oil ratio C / O is selected as 5. The raw oil used is the wax oil of the 3 million t / a catalytic cracking unit of Lanzhou Petrochemical Company, with a molecular weight of 354g / mol and a viscosity of 5.52mm at 100℃. 2 / s, the density at 70℃ is 0.024g / cm 3 , Conradson carbon residue value was 0.07m%. The evaluation conditions of ACE-MODEL C evaluation device were: reaction temperature 515°C, regeneration temperature 715°C, cold trap temperature -13.5°C. The gas product composition was analyzed using INFICON online gas chromatography, and the liquid product composition was analyzed using Agilent 7890B simulated distillation chromatography.
[0073] The physical and chemical properties of LDR-600SR industrial balance agent are shown in Table 2, and the results of ACE evaluation experiment are shown in Table 1. The catalyst surface morphology was characterized using an ULTRA plus thermal field emission scanning electron microscope produced by Carl Zeiss, Germany. The obtained electron microscope images are shown in Figure 1 .
[0074] Example 1
[0075] The raw oil used in this embodiment is a 3 million t / a catalytic cracking unit wax oil of Lanzhou Petrochemical Company to which sodium isooctanoate, calcium stearate, vanadium cyclohexane acid and iron cyclohexane acid are added (sodium isooctanoate, calcium stearate and vanadium cyclohexane acid are added to the raw oil in step (I), and iron cyclohexane acid is added to the raw oil in step (II). The amount of heavy metal sodium, calcium, vanadium and iron on the iron-contaminated industrial balance agent in the comparison agent 1 is used as the target value for feed ratio mixing. The experimental device used is an MCD multi-channel circulation aging device manufactured by 360KAS of the Netherlands with Albemarle patent authorization. Cracking reaction, high temperature regeneration, hydrothermal aging and redox post-treatment are all carried out in the same quartz reactor.
[0076] The test steps are as follows:
[0077] (I) 150g of LDR-600SR fresh agent is added to the above-mentioned MCD circulation aging device, and high-purity nitrogen is used to fluidize the catalyst in the reactor. When the catalyst temperature rises to 510°C, the raw oil doped with sodium isooctanoate, calcium stearate and vanadium cyclohexane acid organic metals that has been preheated to 75°C is introduced into the reactor through the feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal sodium in the raw oil is 350μg / g, the concentration of heavy metal calcium is 170μg / g, and the concentration of heavy metal vanadium is 500μg / g. The raw oil is sprayed from the bottom of the reactor, and the cracking reaction ends after the oil agent contacts for 1.5 minutes, and the oil feeding is stopped.
[0078] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, nitrogen stripping is used for 2 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 30 cycles are performed.
[0079] (II) The feed oil was replaced with a raw oil doped with ferric cyclohexaneate. When the catalyst temperature was stabilized to 510°C, the feed oil preheated to 75°C was introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal iron in the raw oil was 750 μg / g. After the oil-agent contact time of 1.33 minutes, the cracking reaction ended and the oil feeding was stopped.
[0080] Continue to introduce high-purity nitrogen to strip the hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, use nitrogen stripping for 2 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 200 cycles are performed.
[0081] (III) The temperature was raised to a hydrothermal aging temperature of 750°C. The weight ratio of water vapor in the mixed gas was selected to be 50%. After nitrogen stripping for 2 minutes, it was switched to reducing gas for 5 minutes. After nitrogen stripping for 2 minutes, it was switched to oxidizing gas for 5 minutes. After nitrogen stripping again, it entered the next cycle. The flow rates of nitrogen, oxidizing gas and reducing gas were all set to 990 ml / min. The total number of cycles was 90 times, and the hydrothermal aging temperature remained unchanged during all cycles.
[0082] The obtained iron pollution aging simulator was subjected to physicochemical property analysis, and the analysis results are shown in Table 2. 9 g of the above aging simulator was taken for ACE evaluation experiment. The raw oil and operating parameter conditions used were the same as those of Comparative Example 1. The evaluation results are shown in Table 1. The catalyst surface morphology was characterized using an ULTRA plus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany, and the obtained electron microscope images are shown in Figure 2 .
[0083] Example 2
[0084] The feedstock oil used in this embodiment is a 3 million t / a catalytic cracking unit wax oil of Lanzhou Petrochemical Company to which sodium isooctanoate, calcium stearate, vanadium naphthenate, and iron naphthenate are added. The amount of heavy metal sodium, calcium, vanadium, and iron on the iron-contaminated industrial balance agent in the comparison agent 1 is used as the target value for feed ratio mixing. The experimental device used is an MCD multi-channel circulation aging device manufactured by 360KAS of the Netherlands with Albemarle patent authorization. Cracking reaction, high temperature regeneration, hydrothermal aging, and redox post-treatment are all carried out in the same quartz reactor.
[0085] The test steps are as follows:
[0086] (I) 150g of LDR-600SR fresh agent is added to the above-mentioned MCD circulation aging device, and the catalyst is fluidized in the reactor using high-purity nitrogen. When the catalyst temperature rises to 515°C, the organic metal raw oil doped with sodium isooctanoate, calcium stearate and vanadium cyclohexane acid, which has been preheated to 80°C, is introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal sodium in the raw oil is 350μg / g, the concentration of heavy metal calcium is 170μg / g, and the concentration of heavy metal vanadium is 500μg / g. The raw oil is sprayed from the bottom of the reactor, and the cracking reaction ends after the oil agent contacts for 1.33min, and the oil feeding is stopped.
[0087] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 3 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 720°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 35 minutes. After regeneration, nitrogen stripping is used for 3 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 25 cycles are performed.
[0088] (II) The feed oil was replaced with a raw oil doped with ferric cyclohexane. When the catalyst temperature was stabilized to 515°C, the feed oil preheated to 80°C was introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal iron in the raw oil was 750 μg / g. After the oil-agent contacted for 1.5 minutes, the cracking reaction ended and the oil feeding was stopped.
[0089] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 4 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 720°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 35 minutes. After regeneration, nitrogen stripping is used for 4 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 150 cycles are performed.
[0090] (III) The temperature was raised to a hydrothermal aging temperature of 735°C. The water vapor ratio was selected to be 45%, and nitrogen stripping was used for 3 minutes, then switched to reducing gas treatment for 4 minutes, and then nitrogen stripping was used for 3 minutes, then switched to oxidizing gas treatment for 4 minutes, and then nitrogen stripping was used again to enter the next cycle. The flow rates of nitrogen, oxidizing gas and reducing gas were set to 880 ml / min. The total number of cycles was 85 times, and the hydrothermal aging temperature remained unchanged during all cycles.
[0091] The obtained iron pollution aging simulator was subjected to physicochemical property analysis, and the analysis results are shown in Table 2. 9 g of the above aging simulator was taken to perform ACE evaluation experiment. The raw material oil and operating parameter conditions used were the same as those of Comparative Example 1. The evaluation results are shown in Table 1.
[0092] Example 3
[0093] The feedstock oil used in this embodiment is a 3 million t / a catalytic cracking unit wax oil of Lanzhou Petrochemical Company to which sodium isooctanoate, calcium stearate, vanadium naphthenate and iron naphthenate are added. The amount of heavy metal sodium, calcium, vanadium and iron on the iron-contaminated industrial balance agent in the comparison agent 1 is used as the target value for feed proportioning and mixing. The experimental device used is an MCD multi-channel circulation aging device manufactured by 360KAS of the Netherlands with Albemarle patent authorization. Cracking reaction, high temperature regeneration, hydrothermal aging and redox post-treatment are all carried out in the same quartz reactor.
[0094] The test steps are as follows:
[0095] (I) 150g of LDR-600SR fresh agent is added to the above-mentioned MCD circulation aging device, and high-purity nitrogen is used to fluidize the catalyst in the reactor. When the catalyst temperature rises to 500°C, the organic metal raw oil doped with sodium isooctanoate, calcium stearate and vanadium cyclohexane acid, which has been preheated to 70°C, is introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal sodium in the raw oil is 350μg / g, the concentration of heavy metal calcium is 170μg / g, and the concentration of heavy metal vanadium is 500μg / g. The raw oil is sprayed from the bottom of the reactor, and the cracking reaction ends after the oil agent contacts for 1.4 minutes, and the oil feeding is stopped.
[0096] Continue to introduce high-purity nitrogen to strip the hydrocarbon oil and gas. The stripping time is 4 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 710°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 33 minutes. After regeneration, nitrogen stripping is used for 4 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 20 cycles are performed.
[0097] (II) The feed oil was replaced with a raw oil doped with ferric cyclohexaneate. When the catalyst temperature was stabilized at 500°C, the feed oil preheated to 70°C was introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal iron in the raw oil was 750 μg / g. After the oil-agent contact time of 1.4 minutes, the cracking reaction ended and the oil feeding was stopped.
[0098] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 3 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 710°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 33 minutes. After regeneration, nitrogen stripping is used for 3 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 180 cycles are performed.
[0099] (III) The temperature was raised to a hydrothermal aging temperature of 720°C. The water vapor ratio was selected to be 40%, and nitrogen stripping was used for 4 minutes, followed by switching to reducing gas treatment for 3 minutes, and then nitrogen stripping was used for 4 minutes, followed by switching to oxidizing gas treatment for 3 minutes, and then nitrogen stripping was used again to enter the next cycle. The flow rates of nitrogen, oxidizing gas, and reducing gas were set to 1020 ml / min. The total number of cycles was 100, and the hydrothermal aging temperature remained unchanged during all cycles.
[0100] The obtained iron pollution aging simulator was subjected to physicochemical property analysis, and the analysis results are shown in Table 2. 9 g of the above aging simulator was taken to perform ACE evaluation experiment. The raw material oil and operating parameter conditions used were the same as those of Comparative Example 1. The evaluation results are shown in Table 1.
[0101] Comparative Example 2
[0102] The laboratory aging pretreatment of LDR-600SR fresh catalyst was carried out by conventional equal volume impregnation method. The amount of heavy metal iron on the industrial balance in comparative agent 1 was taken as the target, and inorganic iron compounds were used as the iron source.
[0103] The specific steps are as follows:
[0104] (I) 150 g of fresh LDR-600SR catalyst was calcined in a muffle furnace at 600° C. for 2 h and then placed in a desiccator for later use;
[0105] (II) Calculate the amount of iron in the impregnation solution according to the amount of heavy metal iron on the industrial balance agent. Take 150g of deionized water, add 4.34g of ferric chloride, and stir until fully dissolved;
[0106] (III) First, pour the catalyst into the calcination dish, then pour the impregnation solution into it and stir it evenly, then add a small amount of deionized water to ensure that when the calcination dish is slightly shaken, the catalyst surface is uniform and no excess impregnation solution remains. At this time, the total pore volume of the catalyst and the volume of the impregnation solution are equal in volume. Then dry it in a muffle furnace at 150°C for 2h. During the drying process, stir the catalyst intermittently to ensure that no aggregated particles appear. Finally, bake it in a muffle furnace at 600°C for 2h to obtain a heavy metal-loaded catalyst.
[0107] (IV) The heavy metal-loaded catalyst was subjected to a hydrothermal aging post-treatment process at 800°C and 100% water vapor for a total of 15 hours on a multi-sample catalyst rotary hydrothermal aging device. Finally, an aged pre-treated catalyst was obtained. The physicochemical property analysis data of this catalyst are shown in Table 2. The performance of this catalyst was evaluated using an ACE evaluation device. The raw materials and operating parameters used in the evaluation experiment were the same as those in Comparative Example 1. The catalyst surface morphology was characterized using an ULTRAplus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany. The resulting electron microscope images are shown in Table 1. Figure 3 .
[0108] Comparative Example 3
[0109] The laboratory aging pretreatment of LDR-600SR fresh catalyst was carried out by conventional equal volume impregnation method. The amount of heavy metal iron on the industrial balance in comparative agent 1 was taken as the target, and organic iron compound was used as the iron source.
[0110] The specific steps are as follows:
[0111] (I) 150 g of fresh LDR-600SR catalyst was calcined in a muffle furnace at 600° C. for 2 h and then placed in a desiccator for later use;
[0112] (II) Calculate the amount of iron in the impregnation solution according to the amount of heavy metal iron on the industrial balance agent. Take 100g of petroleum ether, add 25g of iron cyclopentaneate, and stir until fully dissolved;
[0113] (III) Pour the catalyst into a calcination dish, then pour the impregnation solution into it and stir evenly, then add a small amount of petroleum ether to ensure that the surface of the catalyst in the calcination dish is uniform and no excess impregnation solution remains when slightly shaken, at which point the total pore volume of the catalyst is equal to the volume of the impregnation solution. Then dry it in a muffle furnace at 150°C for 2h, and stir the catalyst intermittently during the drying process to ensure that no aggregated particles appear. Finally, bake it in a muffle furnace at 600°C for 2h to obtain a heavy metal-loaded catalyst.
[0114] (IV) The heavy metal-loaded catalyst was subjected to a hydrothermal aging post-treatment process at 800°C and 100% water vapor for a total of 15 hours on a multi-sample catalyst rotary hydrothermal aging device. Finally, an aged pre-treated catalyst was obtained. The physicochemical property analysis data of this catalyst are shown in Table 2. The performance of this catalyst was evaluated using an ACE evaluation device. The raw materials and operating parameters used in the evaluation experiment were the same as those in Comparative Example 1. The catalyst surface morphology was characterized using an ULTRAplus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany. The resulting electron microscope images are shown in Table 1. Figure 4 .
[0115] Comparative Example 4
[0116] The LDR-600SR fresh agent was pre-treated in the laboratory using the traditional CD cycle aging contamination method.
[0117] The raw material oil and aging device used in this comparative example are the same as those in Example 1. The target metal amount takes the amount of heavy metal iron on the industrial balance agent as the final loading target, and the iron content in the raw material oil is calculated to be 1650 μg / g.
[0118] The test steps are as follows:
[0119] (I) 150g of LDR-600SR fresh agent was added to the above-mentioned MCD circulation aging device, and high-purity nitrogen was used to fluidize the catalyst in the reactor. When the catalyst temperature rose to 510°C, the raw oil doped with iron cyclohexaneate, which had been preheated to 75°C, was introduced into the reactor through the feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The raw oil was sprayed from the bottom of the reactor, and the cracking reaction ended after the oil-agent contacted for 5 minutes, and the oil feeding was stopped.
[0120] (II) Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 2 minutes, during which the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After the regeneration and burning is completed, the system automatically switches to high-purity nitrogen stripping to remove the oxidizing gas in the system. The stripping time lasts for 3 minutes. At this time, the system opens the reactor furnace door to cool down. When the temperature drops to the cracking reaction temperature, the furnace door is automatically closed to start the next cycle. In this step, all gases are accompanied by a certain proportion of water vapor, and the mass fraction of water vapor in the mixed gas is 50%.
[0121] (III) The above cracking-stripping-regeneration-stripping is one cycle, and a total of 30 cycles are performed to obtain the final aging simulation agent.
[0122] The results of the physicochemical property analysis of the catalyst are shown in Table 2. The performance of the catalyst was evaluated using the ACE evaluation device. The raw materials and operating parameters used in the evaluation experiment were the same as those in Comparative Example 1. The final evaluation results are shown in Table 1. The ULTRA plus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany was used to characterize the surface morphology of the catalyst. The obtained electron microscope images are shown in Table 2. Figure 5 .
[0123] Comparative Example 5
[0124] The raw material oil used in this comparative example is the wax oil of 3 million t / a catalytic cracking unit of Lanzhou Petrochemical Company to which ferric naphthenate is added. The aging device used is the same as that in Example 1. The amount of heavy metal iron on the iron-contaminated industrial balance agent in the comparative agent 1 is used as the target value for feed ratio mixing. The cracking reaction, high temperature regeneration, hydrothermal aging and redox post-treatment are all carried out in the same quartz reactor.
[0125] The test steps are as follows:
[0126] (I) 150 g of LDR-600SR fresh agent was added to the above-mentioned MCD circulation aging device, and the catalyst was fluidized in the reactor using high-purity nitrogen. When the catalyst temperature rose to 510°C, the raw oil doped with ferric cyclohexaneate, which had been preheated to 75°C, was introduced into the reactor through the feed oil pump under the lifting effect of the fluidized high-purity nitrogen to carry out cracking reaction. The concentration of heavy metal iron in the raw oil was 750 μg / g. After the oil-agent contacted for 1.33 minutes, the cracking reaction ended and the oil feeding was stopped.
[0127] Continue to introduce high-purity nitrogen to strip the hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, use nitrogen stripping for 2 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 200 cycles are performed.
[0128] (II) The temperature was raised to a hydrothermal aging temperature of 750°C. The weight ratio of water vapor in the mixed gas was selected to be 50%. After nitrogen stripping for 2 minutes, it was switched to reducing gas for 5 minutes. After nitrogen stripping for 2 minutes, it was switched to oxidizing gas for 5 minutes. After nitrogen stripping again, it entered the next cycle. The flow rates of nitrogen, oxidizing gas and reducing gas were all set to 990 ml / min. The total number of cycles was 90 times, and the hydrothermal aging temperature remained unchanged during all cycles.
[0129] The obtained iron pollution aging simulator was subjected to physicochemical property analysis, and the analysis results are shown in Table 2. 9 g of the above aging simulator was taken for ACE evaluation experiment. The raw oil and operating parameter conditions used were the same as those of Comparative Example 1. The evaluation results are shown in Table 1. The catalyst surface morphology was characterized using an ULTRA plus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany, and the obtained electron microscope images are shown in Figure 6 .
[0130] Comparative Example 6
[0131] The raw oil and aging device used in this comparative example are the same as those in Example 1. The feed ratio is mixed with the target values of the amounts of heavy metals sodium, calcium, vanadium and iron on the iron-contaminated industrial balance agent in comparative agent 1. The cracking reaction, high-temperature regeneration, hydrothermal aging and redox post-treatment are all carried out in the same quartz reactor.
[0132] The test steps are as follows:
[0133] (I) 150g of LDR-600SR fresh agent is added to the above-mentioned MCD circulation aging device, and high-purity nitrogen is used to fluidize the catalyst in the reactor. When the catalyst temperature rises to 510°C, the raw oil doped with sodium isooctanoate, calcium stearate and vanadium cyclohexane acid organic metals that has been preheated to 75°C is introduced into the reactor through the feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal sodium in the raw oil is 350μg / g, the concentration of heavy metal calcium is 170μg / g, and the concentration of heavy metal vanadium is 500μg / g. The raw oil is sprayed from the bottom of the reactor, and the cracking reaction ends after the oil agent contacts for 1.5 minutes, and the oil feeding is stopped.
[0134] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, nitrogen stripping is used for 2 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 30 cycles are performed.
[0135] (II) The feed oil was replaced with a raw oil doped with ferric cyclohexaneate. When the catalyst temperature was stabilized to 510°C, the feed oil preheated to 75°C was introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal iron in the raw oil was 1650 μg / g. After the oil-agent contact time of 1.33 minutes, the cracking reaction ended and the oil feeding was stopped.
[0136] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, use nitrogen stripping for 2 minutes and the system automatically opens the reactor furnace door to cool down.
[0137] (III) The temperature was raised to a hydrothermal aging temperature of 750°C. The weight ratio of water vapor in the mixed gas was selected to be 50%. After nitrogen stripping for 2 minutes, it was switched to reducing gas for 5 minutes. After nitrogen stripping for 2 minutes, it was switched to oxidizing gas for 5 minutes. After nitrogen stripping again, it entered the next cycle. The flow rates of nitrogen, oxidizing gas and reducing gas were all set to 990 ml / min. The total number of cycles was 90 times, and the hydrothermal aging temperature remained unchanged during all cycles.
[0138] The obtained iron pollution aging simulator was subjected to physicochemical property analysis, and the analysis results are shown in Table 2. 9 g of the above aging simulator was taken for ACE evaluation experiment. The raw oil and operating parameter conditions used were the same as those of Comparative Example 1. The evaluation results are shown in Table 1. The catalyst surface morphology was characterized using an ULTRA plus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany, and the obtained electron microscope images are shown in Figure 7 .
[0139] Comparative Example 7
[0140] The raw oil and aging device used in this comparative example are the same as those in Example 1. The feed ratio is mixed with the target values of the amounts of heavy metals sodium, calcium, vanadium and iron on the iron-contaminated industrial balance agent in comparative agent 1. The cracking reaction, high-temperature regeneration, hydrothermal aging and redox post-treatment are all carried out in the same quartz reactor.
[0141] The test steps are as follows:
[0142] (I) 150g of LDR-600SR fresh agent is added to the above-mentioned MCD circulation aging device, and high-purity nitrogen is used to fluidize the catalyst in the reactor. When the catalyst temperature rises to 510°C, the raw oil doped with sodium isooctanoate, calcium stearate and vanadium cyclohexane acid organic metals that has been preheated to 75°C is introduced into the reactor through the feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal sodium in the raw oil is 350μg / g, the concentration of heavy metal calcium is 170μg / g, and the concentration of heavy metal vanadium is 500μg / g. The raw oil is sprayed from the bottom of the reactor, and the cracking reaction ends after the oil agent contacts for 1.5 minutes, and the oil feeding is stopped.
[0143] Continue to introduce high-purity nitrogen to strip and remove hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, nitrogen stripping is used for 2 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 30 cycles are performed.
[0144] (II) The feed oil was replaced with a raw oil doped with ferric cyclohexaneate. When the catalyst temperature was stabilized to 510°C, the feed oil preheated to 75°C was introduced into the reactor through a feed oil pump under the lifting effect of fluidized high-purity nitrogen for cracking reaction. The concentration of heavy metal iron in the raw oil was 750 μg / g. After the oil-agent contact time of 1.33 minutes, the cracking reaction ended and the oil feeding was stopped.
[0145] Continue to introduce high-purity nitrogen to strip the hydrocarbon oil and gas. The stripping time is 2 minutes. During this period, the system begins to gradually heat up. When the catalyst bed temperature reaches 700°C, the system switches to oxidizing gas to start regeneration to remove coke and restore activity. The regeneration time is 30 minutes. After regeneration, use nitrogen stripping for 2 minutes. At the same time, the system automatically opens the reactor furnace door to cool down and prepare for the next cycle reaction. A total of 200 cycles are performed.
[0146] (III) The temperature was raised to a hydrothermal aging temperature of 750°C. The weight ratio of water vapor in the mixed gas was selected to be 50%. After nitrogen stripping for 2 minutes, it was switched to an oxidizing gas for 5 minutes. After nitrogen stripping for 2 minutes, it was switched to a reducing gas for 5 minutes. After nitrogen stripping again, the next cycle began. The flow rates of nitrogen, oxidizing gas, and reducing gas were all set to 990 ml / min. The total number of cycles was 90 times, and the hydrothermal aging temperature remained unchanged during all cycles.
[0147] The obtained iron pollution aging simulator was subjected to physicochemical property analysis, and the analysis results are shown in Table 2. 9 g of the above aging simulator was taken for ACE evaluation experiment. The raw oil and operating parameter conditions used were the same as those of Comparative Example 1. The evaluation results are shown in Table 1. The catalyst surface morphology was characterized using an ULTRA plus thermal field emission scanning electron microscope produced by Carl Zeiss of Germany, and the obtained electron microscope images are shown in Figure 8 .
[0148] As shown in Table 2, the heavy metal level loaded on the aging simulation agent obtained in Examples 1, 2, 3 and Comparative Examples 6 and 7 is substantially the same as that on the industrial balance agent in Comparative Example 1. Comparative Examples 2, 3, 4 and 5 only load heavy metal iron compounds according to conventional aging methods, and the heavy metal iron levels on the obtained aging simulation agents are close to those of the industrial balance agent in Comparative Example 1. The specific surface area of the aging simulation agents in Examples 1, 2 and 3 is close to that in Comparative Example 1. The specific surface area of the aging simulation agents obtained in Comparative Examples 2, 3, 4, 5, 6 and 7 is significantly greater than that in Comparative Example 1. This is because Examples 1, 2 and 3 form an environment conducive to the formation of iron nodules on the catalyst surface through two cycles of aging, a small amount of multiple loadings and a hydrothermal method of first reduction and then oxidation, and finally obtain an aging simulation agent with iron nodules all over the surface. Due to the action of the iron nodules, the pore structure of the catalyst is blocked, resulting in a decrease in specific surface area and a decrease in micro-reaction activity. Although Comparative Examples 2, 3, 4, 5, 6 and 7 are loaded with the same amount of heavy metal iron, they all enter the interior of the catalyst, and no obvious iron nodules are produced on the catalyst surface. Among them, Comparative Example 6 carries out one iron loading, which will cause the metal organic compound to precipitate from the solution before being deposited on the catalyst under the environment of catalytic cracking, and the ideal metal deposition rate cannot be achieved, and effective loading cannot be achieved. The purpose of small amounts and multiple times is to be able to increase the metal loading rate, and all the added iron is deposited on the catalyst. Comparative Example 7 adopts the hydrothermal condition of oxidation followed by reduction, so that each cycle starts with a high valence state of the heavy metal on the catalyst, increasing the destructive effect of the same amount of heavy metal nickel and vanadium on the catalyst. Therefore, these comparative examples cannot truly simulate the pollution effect of heavy metal iron on industrial balance agents.
[0149] As shown in Table 1, although the heavy metal iron loaded on Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6 and Comparative Example 7 is the same as that in Comparative Example 1, since there is basically no iron tumor on the surface of the aging agents obtained by these methods, the pore structure of the catalyst is less affected. Therefore, under the same catalyst-to-oil ratio, compared with Comparative Example 1, the conversion rates of the five aging agents are all higher, the gasoline yield and the liquefied gas yield are also higher, and the heavy oil and diesel yields are lower.
[0150] The aging simulation agents of Examples 1, 2, and 3 obtained by the method of the present invention can better match the iron-contaminated industrial balance agent in the distribution of multiple important products such as coke, hydrogen yield, and gasoline and diesel yield, achieving a true simulation effect for the industrial balance agent.
[0151] Depend on Figure 1 As shown, under the influence of iron pollution, a large number of tumor-like protrusions, namely iron tumors, obviously appear on the surface of LDR-600SR industrial balance agent. Figure 2 A large number of iron nodules were also observed on the surface of the catalyst. Figure 3 As shown in the figure, inorganic ferric chloride is used as the iron source, and the loaded iron basically enters the interior of the catalyst, so there is basically no nodular protrusion on the catalyst surface. Figure 4 As shown), Comparative Example 4 ( Figure 5 As shown) and Comparative Example 5 ( Figure 6 As shown in the figure, organic cyclopentane iron is used as the iron source, and a small amount of iron nodules are generated on the catalyst surface, but they are not very obvious. Figure 7 The metal was precipitated from the solution before being deposited on the catalyst, and there was basically no nodular protrusion. Figure 8 The hydrothermal method of oxidation followed by reduction increases the destructive effect of heavy metals nickel and vanadium on the catalyst. Therefore, the method of the present invention can more realistically simulate the actual situation of industrial iron pollution.
[0152] Table 1
[0153]
[0154] Table 2
[0155]
[0156]
[0157] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the present invention.
Claims
1. A method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst, characterized in that: The steps include: Step 1, reacting the first feedstock oil with a fresh catalytic cracking catalyst, then stripping to remove hydrocarbon oil gas, then performing charring regeneration, then stripping to cool, and then allowing the treated catalytic cracking catalyst to cycle with the first feedstock oil to perform a reaction, stripping, regeneration, and stripping process, the number of cycles being at least one; Step 2, reacting the second raw oil with the catalytic cracking catalyst obtained in step 1, then stripping to remove hydrocarbon oil gas, then performing charring regeneration, then stripping to cool, and then allowing the treated catalytic cracking catalyst to cycle with the second raw oil to perform reaction, stripping, regeneration, and stripping, the number of cycles being at least one; Step 3, subjecting the catalytic cracking catalyst obtained in step 2 to a hydrothermal aging treatment to obtain an industrial iron-contaminated catalytic cracking catalyst; Wherein, alkali metal compounds, alkaline earth metal compounds and / or transition metal compounds other than iron are added to the first feedstock oil, and iron-containing compounds are added to the second feedstock oil.
2. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 1, characterized in that: The alkali metal compound is a sodium-containing organic compound, the alkaline earth metal compound is a calcium-containing organic compound, the transition metal compound other than iron is at least one of a nickel-containing organic compound, a vanadium-containing organic compound, and a copper-containing organic compound; and the iron-containing compound is an iron-containing organic compound.
3. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 2, characterized in that: The alkali metal compound is sodium isooctanoate and / or sodium naphthenate, the alkaline earth metal compound is calcium stearate, the transition metal compound other than iron is nickel naphthenate, vanadium naphthenate or copper naphthenate; the iron-containing compound is at least one of iron naphthenate, iron stearate and ferrocene.
4. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 1, characterized in that: The metal concentration in the first stock oil is 100 μg / g to 2000 μg / g in terms of metal; and the metal concentration in the second stock oil is 100 μg / g to 2000 μg / g in terms of metal.
5. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 1, characterized in that: The first raw oil reacts with the fresh catalytic cracking catalyst after preheating, the preheating temperature is 60°C to 90°C, the reaction temperature is 490°C to 530°C, the catalyst-oil ratio is 5 to 30, the single cycle oil feeding time is 1min to 5min, and the mass flow rate of the first raw oil is 5g / min to 15g / min; the second raw oil reacts with the catalytic cracking catalyst obtained in step 1 after preheating, the preheating temperature is 60°C to 90°C, the reaction temperature is 490°C to 530°C, the catalyst-oil ratio is 5 to 30, the single cycle oil feeding time is 1min to 5min, and the mass flow rate of the first raw oil is 5g / min to 15g / min.
6. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 1, characterized in that: In step 1, the stripping to remove hydrocarbon oil and gas and the stripping cooling are both carried out under the action of nitrogen, the nitrogen flow rate is 500ml / min~1500ml / min, and the nitrogen stripping time is 1min~10min; the temperature of the char regeneration is 680℃~740℃, and the char regeneration time is 20min~40min.
7. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 1, characterized in that: In step 2, the stripping to remove hydrocarbon oil and gas and the stripping cooling are both carried out under the action of nitrogen, the nitrogen flow rate is 500ml / min~1500ml / min, and the nitrogen stripping time is 1min~10min; the temperature of the char regeneration is 680℃~740℃, and the char regeneration time is 20min~40min.
8. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 1, characterized in that: Step 3: The hydrothermal aging treatment process includes: The catalytic cracking catalyst obtained in step 2 is treated with a reducing gas, then treated with nitrogen, then treated with an oxidizing gas, and then treated with nitrogen. The process of treating with a reducing gas, treating with nitrogen, treating with an oxidizing gas, and treating with nitrogen is then repeated at least once to obtain an industrial iron-contaminated catalytic cracking catalyst.
9. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 8, characterized in that: The catalytic cracking catalyst obtained in step 2 is introduced with a certain amount of water vapor during the treatment with reducing gas, nitrogen and oxidizing gas, and the mass ratio of water vapor to reducing gas, water vapor to nitrogen and water vapor to oxidizing gas is 30:70-55:45; the oxidizing gas includes one or more of high-purity air, oxygen in nitrogen and sulfur dioxide in nitrogen; the selected reducing gas includes one or more of hydrogen in nitrogen, propylene in nitrogen and carbon monoxide in nitrogen; the temperature for the treatment with the reducing gas is 7 The temperature of the nitrogen treatment is 700℃~770℃, the time is 1min~10min, and the flow rate of the nitrogen is 500ml / min~1500ml / min; the temperature of the oxidizing gas treatment is 700℃~770℃, the time is 2min~7min, and the flow rate of the oxidizing gas is 500ml / min~1500ml / min.
10. The method for simulating the preparation of an industrial iron-contaminated catalytic cracking catalyst according to claim 8, characterized in that: The number of cycles of step 1 is 10 to 40 times, the number of cycles of step 2 is 100 to 300 times, and the number of cycles of step 3 is 75 to 120 times.
Citation Information
Patent Citations
Metal contaminating and water thermal aging method for catalytic cracking catalyst
CN105562121A
Catalyst heavy metal cycle pollution ageing reactor
CN106824022A
Catalyst hydrothermal ageing device and ageing method
CN106841506A
Hydrocarbon oil conversion method and device
CN114426859A
Cyclic polluting and ageing process for catalyst
CN1382528A